EFFECT OF ONLINE EDUCATION ON INCREASING KNOWLEDGE ABOUT KEEP YOUR TEETH CLEAN AND MOUTH OF STUDENTS OF CLASS VIII-2 SMP STATE 1 DARUL IMARAH - Nadya Hafiza Sara Ate; Salfiyadi, Teuku (Journal Dental Health, 2022)
Education or education is the provision of one's knowledge and abilities through learning, so that a person or group of people who receive education can do as expected by educators, from those who do not know to know and from those who are unable to cope with their own health to become independent. This study aims to determine the effect of online education on increasing knowledge about maintaining dental and oral hygiene. The type of research used is a quasi-experimental design with one group pre-test and post-test design. Conducted at SMPN 1 Darul Imarah, data collection was carried out using a questionnaire. The population in this study amounted to 30 students. The sample used is 30 students using total sampling. The results showed an increase in the mean value of students' knowledge after intervention with online education was 17.5 from pretest 67.83 to 85.33 at posttest, data processing used statistical tests, Paired Sample T-Test p = 0.000 (p = < 0.05). The conclusion is that there is an effect of online education on increasing knowledge about maintaining dental and oral hygiene. Suggestions are expected for teachers and dental health workers to cooperate in providing guidance and counseling about dental and oral hygien.